Reassessing single-stent techniques for isolated left anterior descending ostial disease: a two-year intravascular ultrasound-guided retrospective comparison of precise ostial, floating, and crossover stenting strategies - Xi Wu; Mingxing Wu; Haobo Huang; Zhe Liu; He Huang; Lei Wang (BMC Cardiovascular Disorders)
Abstract Background/Objectives Percutaneous coronary intervention (PCI) for isolated left anterior descending (LAD) ostial lesions remains challenging, with limited comparative data on stenting strategies. We aimed to evaluate the procedural and long-term outcomes of three single-stent techniques: precise ostial stenting (POS), floating stenting (FS), and crossover stenting (CS). Methods In this retrospective study, 116 patients with isolated LAD ostial disease underwent intravascular ultrasound (IVUS)-guided PCI using one of the three strategies. Baseline characteristics, procedural details, IVUS findings, and major adverse cardiac and cerebrovascular events (MACCEs) over two years were compared. Results Compared to POS and FS, CS resulted in larger minimal stent area at the ostium, and a higher rate of complete stent coverage (100% vs. 39.5% and 23.1%, p < 0.001). At 2-year follow-up, MACCE rates were significantly lower in the CS group (2.6%) compared to FS (13.5%) and POS (15.8%, p = 0.039), mainly due to reduced target lesion revascularization. FS showed improved coverage compared to POS, but inferior angiographic outcomes and higher event rates than CS. Conclusions In IVUS-guided PCI for isolated LAD ostial lesions, CS offers superior ostial coverage and clinical outcomes. FS may serve as a compromise when anatomical constraints limit crossover. These findings support a tailored strategy based on lesion characteristics and IVUS assessment.